Comparison of Cyclosporine and Steroids in Treating Severe Allergic Conjunctivitis in Children: an Evidence-based Case Report - Muhammad Ilham Dhiya Rakasiwi; Julie Dewi Barliana; Afid Brilliana Putra; Muhammad Imran Khan Ismail; Awliya Awliya; Gusti Candra Pamungkas; Nida Ghitha Aulia (Faculty of Medicine, Universitas Jember, 2024)
The efficacy of cyclosporine compared with corticosteroid in reducing symptoms and signs in children with severe allergic conjunctivitis, either in vernal keratoconjunctivitis or atopic keratoconjunctivitis, is still unknown. Here we present the case of an 8-year-old boy with a case of allergic keratoconjunctivitis. The patient had been given steroid eye drops (Dexamethasone 1 mg) for 2 weeks and only slight improvement was found. Considering the steroid’s long-term effects, the doctor prescribed cyclosporine eye drops. Therefore, this case study is conducted to compare the better efficacy between cyclosporine eye drops and steroid eye drops as a treatment for severe allergic conjunctivitis. After conducting a systematic literature analysis following the PRISMA guidelines, full-text analysis was carried out on two RCTs by assessing their validity, clinical importance, and applicability according to the Oxford CEBM criteria. One of the studies did not meet the validity criteria, while another study showed that cyclosporine eye drops that were given to patients with severe vernal keratoconjunctivitis could reduce signs and symptoms. There was no significant difference between cyclosporine eye drops and dexamethasone eye drops. Cyclosporine's function to reduce signs and symptoms of severe allergic conjunctivitis in children is equivalent to that of corticosteroids. Keywords: Cyclosporine, corticosteroid, severe allergic conjunctivitis, therapy